1989
DOI: 10.2519/jospt.1989.11.3.108
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Values Generated During Testing of the Knee Using the Cybex II Plus®and Biodex Model B-2000®Isokinetic Dynamometers

Abstract: Forty-eight, healthy, adult, volunteer subjects (20 males, 28 females) who ranged in age from 21-46 years were studied during isokinetic testing of the knee joint. The same knee of each subject was tested at speeds of 60, 180, and 240°/sec on both the Biodex Model 8-2000" and the Cybex I 1 Plus' isokinetic dynamometers. The following variables were compared: peak torques, angle of peak torques, peak torque to body weight ratios, and flexion to extension ratios. Analysis of correlation coefficients showed stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0
7

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 18 publications
(24 reference statements)
2
15
0
7
Order By: Relevance
“…The highest reproducibility for measured isokinetic muscle strength is achieved at velocities below 100°s )1 (Baltzopoulos & Brodie, 1989;Thompson et al, 1989;Gross et al, 1991). When comparing the total work (in Watt), no significant difference was observed for knee or elbow, or for flexion or extension (data not presented).…”
Section: Comparison Of Biodex and Lidomentioning
confidence: 97%
See 1 more Smart Citation
“…The highest reproducibility for measured isokinetic muscle strength is achieved at velocities below 100°s )1 (Baltzopoulos & Brodie, 1989;Thompson et al, 1989;Gross et al, 1991). When comparing the total work (in Watt), no significant difference was observed for knee or elbow, or for flexion or extension (data not presented).…”
Section: Comparison Of Biodex and Lidomentioning
confidence: 97%
“…Earlier studies comparing different isokinetic devices indicate difficulties in extrapolating results from one device to another (Thompson et al, 1989;Gross et al, 1991). A comparison of different isokinetic devices seems necessary since good intermachine reliability may reflect the validity of each instrument.…”
Section: Introductionmentioning
confidence: 99%
“…2 [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Harding et al studied test-retest reliability of concentric peak and average torques of the knee extensor and flexor muscles using the Kin-Com. '3 Feiring el at measured peak torque and total work output of knee extensor and flexor muscles using the Biodex dynamo-meter.30 In both studies, high test-retest reliability interclass correlation coefficients (ICCs) were shown (ICCs 0-936 and 0-952, respectively).…”
mentioning
confidence: 99%
“…No statistical difference in peak torque was found for knee flexion and extension at 60°/sec and for knee flexion at 180°/sec. Thompson et al (13) reported that the intermachine reliability between Cybex and Biodex measurements of knee flexion and extension torque using the Pearson correlation coefficient ranged between 0.80 and 0.90, but that Cybex and Biodex measurements differed significantly for some variables as assessed by paired t-testing.…”
mentioning
confidence: 99%